Preparation method of Ti3C2Tx MXene / graphite composite conductive ink with low resistance temperature coefficient

By preparing Ti3C2Tx MXene/graphite composite conductive ink with low resistance temperature coefficient, the problem of significant change in the resistance between Ti3C2Tx MXene nanosheets when the temperature rises, significantly improving the sensing accuracy of the strain sensor at higher temperatures.

CN119875433APending Publication Date: 2025-04-25HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510120393.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The interlayer resistance of Ti3C2Tx MXene nanosheets changes significantly as the temperature rises, resulting in a decrease in the sensing accuracy of the strain sensor based on Ti3C2Tx MXene at higher temperatures.

Method used

Using the preparation method of Ti3C2Tx MXene/graphite composite conductive ink, a composite conductive ink with a low resistance temperature coefficient was prepared by adding Ti3C2Tx MXene powder and nanographite powder to the mixture of terpineol and isopropanol containing ethyl cellulose, and by regulating the ratio between the various components and the preparation process.

Benefits of technology

Within the range of temperature rise from 30°C to 70°C, the relative resistance of the composite conductive ink changes no more than 0.06%, and the absolute value of the average resistance temperature coefficient is not higher than 1.5×10-5/°C, which significantly improves the sensing accuracy of the strain sensor at higher temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875433A_ABST
    Figure CN119875433A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of Ti < 3 > C < 2 > T < x > MXene / graphite composite conductive ink with a low resistance temperature coefficient. The method comprises the following steps: 1, preparing a Ti < 3 > C < 2 > T < x > MXene dispersion liquid; (2) preparing Ti < 3 > C < 2 > T < x > MXene powder; and 3, preparing the Ti < 3 > C < 2 > T < x > MXene / graphite composite conductive ink. The Ti < 3 > C < 2 > T < x > MXene powder and the nano graphite powder are added into a terpilenol and isopropanol mixture containing ethyl cellulose, and the Ti < 3 > C < 2 > T < x > MXene / graphite composite conductive ink with the low resistance temperature coefficient is finally prepared by regulating and controlling the proportion of all the component materials and a preparation process. When the temperature of the prepared composite conductive ink rises from 30 DEG C to 70 DEG C, the relative resistance change is not higher than 0.06%, and the absolute value of the average resistance temperature coefficient is not higher than 1.5 * 10 <-5 > / DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of material science and relates to a method for preparing a conductive ink, and more particularly to a Ti3C2T3 conductive ink having a low temperature coefficient of resistance. x Preparation method of MXene / graphite composite conductive ink. Background Art

[0002] Ti3C2T x MXene is a two-dimensional nanosheet material with good electrical conductivity and has been widely used in various high-performance strain sensors. However, as the temperature rises, Ti3C2T x The detachment of water molecules between MXene layers will cause a significant change in the interlayer resistance of MXene nanosheets. x The resistance change of MXene strain sensing materials is significantly affected by both strain and temperature, which causes the corresponding strain sensors to have a decreased sensing accuracy at higher temperatures. Summary of the invention

[0003] In order to broaden the Ti3C2T x The application scenarios of MXene strain sensing materials at higher temperatures. The present invention provides a Ti3C2T3 with low temperature coefficient of resistance. x A method for preparing a MXene / graphite composite conductive ink. The composite conductive ink prepared by the method can exhibit a temperature coefficient of resistance close to 0 within a certain temperature range, that is, the resistance of the composite conductive ink does not change significantly with changes in the external temperature within a certain temperature range.

[0004] The objective of the present invention is achieved through the following technical solutions:

[0005] A Ti3C2T with low temperature coefficient of resistance x The preparation method of MXene / graphite composite conductive ink comprises the following steps:

[0006] Step 1: Ti3C2T x Preparation of MXene dispersion:

[0007] Step 11, dissolving 0.1-10 g of lithium fluoride into 5-100 ml of a hydrochloric acid solution having a concentration of 1-12 mol / L to obtain a hydrochloric acid / lithium fluoride etching solution;

[0008] Step 1 and 2, slowly add 0.1-10g of titanium aluminum carbide powder into 5-100ml of hydrochloric acid / lithium fluoride etching solution, magnetically stir the mixture at 20-80°C, control the stirring speed to 200-3000r / min, and react for 10-50h;

[0009] Step 1-3, centrifuge the solution after the reaction several times, control the speed of the centrifugal process to 1500-10000 r / min, until the pH value of the upper liquid is 5-7, pour out the upper liquid, and retain the lower precipitate;

[0010] Step 14: Add 30-50 ml of deionized water to the lower precipitate obtained after centrifugation, and vortex on a vortex oscillator for 5-60 minutes;

[0011] Step 15: centrifuge the vortexed solution at a speed of 500 to 5000 r / min, and collect 5 to 30 ml of supernatant;

[0012] Step 16: Continue to repeat steps 14 and 15, collect the supernatant, and obtain Ti3C2T x MXene dispersion;

[0013] Step 2: Ti3C2T x Preparation of MXene powder:

[0014] Step 21: Ti3C2T obtained in step 1 x The MXene dispersion is frozen, the freezing temperature is controlled to be -50 to -5°C, and the freezing time is 12 to 36 hours;

[0015] Step 22: The Ti3C2T x The MXene frozen material is placed in a freeze dryer for freeze drying, and the freeze drying time is controlled to be 5 to 7 days;

[0016] Step 2 and 3: freeze-dried Ti3C2T x The MXene porous aerogel was ground to obtain Ti3C2T with a particle size of 10 to 100 μm. x MXene powder;

[0017] Step 3: Ti3C2T x Preparation of MXene / graphite composite conductive ink:

[0018] Step 3: 1. Mix 0.1-10 ml of terpineol and 0.1-10 ml of isopropyl alcohol, and stir them evenly by magnetic stirring;

[0019] Step 32: Add 0.1-2 g of ethyl cellulose to the mixed solution, and stir the mixed solution magnetically at 40-90° C., control the stirring speed to 300-2000 r / min, and the stirring time to 0.5-12 h;

[0020] Step 3: Add 0.01-2g of Ti3C2Tx MXene powder and 0.01-2 g of nanographite powder are added to the mixed solution obtained in step 3-2, and magnetic stirring is performed at 40-90° C. The stirring speed is controlled at 300-2000 r / min, and the stirring time is 0.5-12 h;

[0021] Step 34: The mixed solution obtained in step 33 is subjected to open magnetic stirring at 80-250°C, the stirring speed is controlled to be 300-2000 r / min, and the stirring time is 0.5-12 h to obtain Ti3C2T x MXene / graphite composite conductive ink.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] The present invention adopts Ti3C2T x MXene powder and nanographite powder were added to a mixture of pine alcohol and isopropyl alcohol containing ethyl cellulose. By adjusting the ratio of each component material and the preparation process, Ti3C2T with a low temperature coefficient of resistance was finally prepared. x MXene / graphite composite conductive ink. When the temperature of the composite conductive ink prepared by the present invention rises from 30°C to 70°C, the relative resistance change is no more than 0.06%, and the absolute value of the average resistance temperature coefficient is no more than 1.5×10 -5 / ℃. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Ti3C2T obtained in Example 1-4 x Relative resistance change of MXene / graphite composite conductive ink as a function of temperature. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0026] Embodiment 1:

[0027] Step 1: Ti3C2T xPreparation of MXene dispersion: 1.6 g lithium fluoride was dissolved in 20 ml hydrochloric acid solution with a concentration of 9 mol / L to obtain hydrochloric acid / lithium fluoride etching solution; then 1 g titanium aluminum carbide powder was slowly added to 20 ml etching solution, and the mixed solution was magnetically stirred at 50 ° C, the stirring speed was controlled to 800 r / min, and the reaction was carried out for 30 hours; the solution after the reaction treatment was centrifuged several times until the pH value of the upper liquid was 6, and the speed of the centrifugal process was controlled to 3500 r / min; then 50 ml of deionized water was added to the lower precipitate after centrifugation, and vortexed in a vortex oscillator for 20 minutes; then the vortexed solution was centrifuged, the speed of the centrifugal process was controlled to 1500 r / min, and 15 ml of supernatant was collected; deionized water was added to the remaining solution to 50 ml, and the above vortex and centrifugation process was repeated to obtain Ti3C2T x MXene dispersion.

[0028] Step 2: Ti3C2T x Preparation of MXene powder: Ti3C2T obtained in step 1 x The MXene dispersion was frozen, and the freezing temperature was controlled to be -18 °C for 24 h. The obtained MXene frozen product was then placed in a freeze dryer for drying, and the drying time was controlled to be 7 days. Finally, the freeze-dried MXene aerogel was ground to obtain Ti3C2T4 with a particle size of 10 to 100 μm. x MXene powder.

[0029] Step 3: Ti3C2T x Preparation of MXene / graphite composite conductive ink: 2.5 ml of pine alcohol and 7.5 ml of isopropanol were mixed and mixed evenly by magnetic stirring; 0.5 g of ethyl cellulose was added to the mixed solution, and the mixed solution was magnetically stirred at 70 ° C for 2 h, and the stirring speed was controlled at 1500 r / min; then 0.01 g of Ti3C2T x MXene powder and 0.5 g of nano-graphite powder were added to the mixture and magnetically stirred for 2 h, and the stirring speed was controlled at 1500 r / min; finally, the mixture was openly magnetically stirred at 150 °C for 2 h, and the stirring speed was controlled at 1000 r / min to obtain Ti3C2T x MXene / graphite composite conductive ink.

[0030] The Ti3C2T x When the temperature of MXene / graphite composite conductive ink rises from 30℃ to 70℃, the relative resistance changes by 2.037%, and the average temperature coefficient of resistance in the temperature range is 5.1×10 -4 / ℃.

[0031] Embodiment 2:

[0032] Step 1: Ti3C2T x Preparation of MXene dispersion: 1.6 g lithium fluoride was dissolved in 20 ml hydrochloric acid solution with a concentration of 9 mol / L to obtain hydrochloric acid / lithium fluoride etching solution; then 1 g titanium aluminum carbide powder was slowly added to 20 ml etching solution, and the mixed solution was magnetically stirred at 50 ° C, the stirring speed was controlled to 800 r / min, and the reaction was carried out for 30 hours; the solution after the reaction treatment was centrifuged several times until the pH value of the upper liquid was 6, and the speed of the centrifugal process was controlled to 3500 r / min; then 50 ml of deionized water was added to the lower precipitate after centrifugation, and vortexed in a vortex oscillator for 20 minutes; then the vortexed solution was centrifuged, the speed of the centrifugal process was controlled to 1500 r / min, and 15 ml of supernatant was collected; deionized water was added to the remaining solution to 50 ml, and the above vortex and centrifugation process was repeated to obtain Ti3C2T x MXene dispersion.

[0033] Step 2: Ti3C2T x Preparation of MXene powder: Ti3C2T obtained in step 1 x The MXene dispersion was frozen, and the freezing temperature was controlled to be -18 °C for 24 h. The obtained MXene frozen product was then placed in a freeze dryer for drying, and the drying time was controlled to be 7 days. Finally, the freeze-dried MXene aerogel was ground to obtain Ti3C2T4 with a particle size of 10 to 100 μm. x MXene powder.

[0034] Step 3: Ti3C2T x Preparation of MXene / graphite composite conductive ink: 2.5 ml of pine alcohol and 7.5 ml of isopropanol were mixed and mixed evenly by magnetic stirring; 0.5 g of ethyl cellulose was added to the mixed solution, and the mixed solution was magnetically stirred at 70 ° C for 2 h, and the stirring speed was controlled at 1500 r / min; then 0.05 g of Ti3C2T x MXene powder and 0.45 g of nano-graphite powder were added to the mixture and magnetically stirred for 2 h, and the stirring speed was controlled at 1500 r / min; finally, the mixture was openly magnetically stirred at 150 °C for 2 h, and the stirring speed was controlled at 1000 r / min to obtain Ti3C2T x MXene / graphite composite conductive ink.

[0035] The Ti3C2T xWhen the temperature of MXene / graphite composite conductive ink rises from 30℃ to 70℃, the relative resistance changes by 0.052%, and the average resistance temperature coefficient in the temperature range is 1.3×10 -5 / ℃.

[0036] Embodiment 3:

[0037] Step 1: Ti3C2T x Preparation of MXene dispersion: 1.6 g lithium fluoride was dissolved in 20 ml hydrochloric acid solution with a concentration of 9 mol / L to obtain hydrochloric acid / lithium fluoride etching solution; then 1 g titanium aluminum carbide powder was slowly added to 20 ml etching solution, and the mixed solution was magnetically stirred at 50 ° C, the stirring speed was controlled to 800 r / min, and the reaction was carried out for 40 hours; the solution after the reaction treatment was centrifuged several times until the pH value of the upper liquid was 6, and the speed of the centrifugal process was controlled to 3500 r / min; then 50 ml of deionized water was added to the lower precipitate after centrifugation, and vortexed in a vortex oscillator for 20 minutes; then the vortexed solution was centrifuged, the speed of the centrifugal process was controlled to 1500 r / min, and 15 ml of supernatant was collected; deionized water was added to the remaining solution to 50 ml, and the above vortex and centrifugation process was repeated to obtain Ti3C2T x MXene dispersion.

[0038] Step 2: Ti3C2T x Preparation of MXene powder: Ti3C2T obtained in step 1 x The MXene dispersion was frozen, and the freezing temperature was controlled to be -18 °C for 24 h. The obtained MXene frozen product was then placed in a freeze dryer for drying, and the drying time was controlled to be 7 days. Finally, the freeze-dried MXene aerogel was ground to obtain Ti3C2T4 with a particle size of 10 to 100 μm. x MXene powder.

[0039] Step 3: Ti3C2T x Preparation of MXene / graphite composite conductive ink: 2.5 ml of pine alcohol and 7.5 ml of isopropanol were mixed and mixed evenly by magnetic stirring; 0.5 g of ethyl cellulose was added to the mixed solution, and the mixed solution was magnetically stirred at 70 ° C for 2 h, and the stirring speed was controlled at 1500 r / min; then 0.1 g of Ti3C2T x MXene powder and 0.4 g of nano-graphite powder were added to the mixture and magnetically stirred for 2 h, and the stirring speed was controlled at 1500 r / min; finally, the mixture was openly magnetically stirred at 150 ° C for 2 h, and the stirring speed was controlled at 1000 r / min to obtain MXene-based composite conductive ink.

[0040] The Ti3C2T x When the temperature of MXene / graphite composite conductive ink rises from 30℃ to 70℃, the relative resistance changes by -0.047%, and the average temperature coefficient of resistance in the temperature range is -1.175×10 -5 / ℃.

[0041] Example 4

[0042] Step 1: Ti3C2T x Preparation of MXene dispersion: 1.6 g lithium fluoride was dissolved in 20 ml hydrochloric acid solution with a concentration of 9 mol / L to obtain hydrochloric acid / lithium fluoride etching solution; then 1 g titanium aluminum carbide powder was slowly added to 20 ml etching solution, and the mixed solution was magnetically stirred at 50 ° C, the stirring speed was controlled to 800 r / min, and the reaction was carried out for 30 hours; the solution after the reaction treatment was centrifuged several times until the pH value of the upper liquid was 6, and the speed of the centrifugal process was controlled to 3500 r / min; then 50 ml of deionized water was added to the lower precipitate after centrifugation, and vortexed in a vortex oscillator for 20 minutes; then the vortexed solution was centrifuged, the speed of the centrifugal process was controlled to 1500 r / min, and 15 ml of supernatant was collected; deionized water was added to the remaining solution to 50 ml, and the above vortex and centrifugation process was repeated to obtain Ti3C2T x MXene dispersion.

[0043] Step 2: Ti3C2T x Preparation of MXene powder: Ti3C2T obtained in step 1 x The MXene dispersion was frozen, and the freezing temperature was controlled to be -18 °C for 24 h. The obtained MXene frozen product was then placed in a freeze dryer for drying, and the drying time was controlled to be 7 days. Finally, the freeze-dried MXene aerogel was ground to obtain Ti3C2T4 with a particle size of 10 to 100 μm. x MXene powder.

[0044] Step 3: Ti3C2T x Preparation of MXene / graphite composite conductive ink: 2.5 ml of pine alcohol and 7.5 ml of isopropanol were mixed and mixed evenly by magnetic stirring; 0.5 g of ethyl cellulose was added to the mixed solution, and the mixed solution was magnetically stirred at 70 ° C for 2 h, and the stirring speed was controlled at 1500 r / min; then 0.15 g of Ti3C2T xMXene powder and 0.35 g of nano-graphite powder were added to the mixture and magnetically stirred for 2 h, and the stirring speed was controlled at 1500 r / min; finally, the mixture was openly magnetically stirred at 150 ° C for 2 h, and the stirring speed was controlled at 1000 r / min to obtain MXene-based composite conductive ink.

[0045] The Ti3C2T x When the temperature of MXene / graphite composite conductive ink rises from 30℃ to 70℃, the relative resistance changes by -1.163%, and the average resistance temperature coefficient in the temperature range is -2.9×10 -4 / ℃.

[0046] Figure 1 The Ti3C2T obtained in Example 1-4 x The resistance of MXene / graphite composite conductive ink varies with temperature. Figure 1 It can be seen that the resistance of the composite conductive inks prepared with different mass ratios of graphite powder and MXene powder varies significantly with temperature. x The relative resistance changes of the MXene / graphite composite conductive ink in the temperature range from 30°C to 70°C are 0.052% (Example 2) and -0.047% (Example 3). The relative resistance changes of Example 2 in this temperature range are less than or equal to 0.052% (can be regarded as close to 0), and the relative resistance change of Example 3 in this temperature range is up to -0.301% (when the temperature rises from 30°C to 40°C). Therefore, the Ti3C2T2O3 obtained in Example 2 is x The resistance temperature coefficient of MXene / graphite composite conductive ink is optimal.

Claims

1. A Ti3C2T with low temperature coefficient of resistance x A method for preparing a MXene / graphite composite conductive ink, characterized in that The method comprises the following steps: Step 1: Ti3C2T x Preparation of MXene dispersion: Step 11, dissolving 0.1-10 g of lithium fluoride into 5-100 ml of a hydrochloric acid solution having a concentration of 1-12 mol / L to obtain a hydrochloric acid / lithium fluoride etching solution; Step 1 and 2, slowly add 0.1-10 g of titanium aluminum carbide powder into 5-100 ml of hydrochloric acid / lithium fluoride etching solution, and magnetically stir the mixture at 20-80° C.; Step 1-3: Centrifuge the solution after the reaction several times until the pH value of the upper liquid is 5-7, pour out the upper liquid, and keep the lower precipitate; Step 14: Add 30-50 ml of deionized water to the lower precipitate obtained after centrifugation, and vortex on a vortex oscillator for 5-60 minutes; Step 15: Centrifuge the vortexed solution and collect 5-30 ml of supernatant; Step 16: Continue to repeat steps 14 and 15, collect the supernatant, and obtain Ti3C2T x MXene dispersion; Step 2: Ti3C2T x Preparation of MXene powder: Step 21: Ti3C2T obtained in step 1 x The MXene dispersion is frozen; Step 22: The Ti3C2T x The MXene frozen material is placed in a freeze dryer for freeze drying; Step 2 and 3: freeze-dried Ti3C2T x MXene porous aerogel is ground to obtain Ti3C2T x MXene powder; Step 3: Ti3C2T x Preparation of MXene / graphite composite conductive ink: Step 3:

1. Mix 0.1-10 ml of terpineol and 0.1-10 ml of isopropyl alcohol, and stir them evenly by magnetic stirring; Step 32: Add 0.1-2 g of ethyl cellulose to the mixture, and stir the mixture magnetically at 40-90° C.; Step 3: Add 0.01-2g of Ti3C2T x MXene powder and 0.01-2 g of nanographite powder are added to the mixed solution obtained in step 3-2, and magnetic stirring is performed at 40-90°C; Step 34: The mixed solution obtained in step 33 is subjected to open magnetic stirring at 80-250°C to obtain Ti3C2T x MXene / graphite composite conductive ink.

2. The Ti3C2T3O3 composite material with low temperature coefficient of resistance according to claim 1 x A method for preparing a MXene / graphite composite conductive ink, characterized in that In the steps 1 and 2, the stirring speed is controlled to be 200 to 3000 r / min, and the reaction is carried out for 10 to 50 hours.

3. The Ti3C2T3O3 composite material with low temperature coefficient of resistance according to claim 1 x A method for preparing a MXene / graphite composite conductive ink, characterized in that In the steps 1 to 3, the rotation speed of the centrifugal process is controlled to be 1500 to 10000 r / min.

4. The Ti3C2T3O4 composite material with low temperature coefficient of resistance according to claim 1 x A method for preparing a MXene / graphite composite conductive ink, characterized in that In the step 15, the rotation speed of the centrifugal process is controlled to be 500-5000 r / min.

5. The Ti3C2T3O4 composite material with low temperature coefficient of resistance according to claim 1 x A method for preparing a MXene / graphite composite conductive ink, characterized in that In the step 21, the freezing temperature is controlled to be -50 to -5°C, and the freezing time is 12 to 36 hours.

6. The Ti3C2T3O4 composite material having a low temperature coefficient of resistance according to claim 1 x A method for preparing a MXene / graphite composite conductive ink, characterized in that In the step 22, the freeze-drying time is controlled to be 5 to 7 days.

7. The Ti3C2T3O4 composite material having a low temperature coefficient of resistance according to claim 1 x A method for preparing a MXene / graphite composite conductive ink, characterized in that In the steps 2 and 3, Ti3C2T x The particle size of MXene powder is 10 to 100 μm.

8. The Ti3C2T3O4 composite material having a low temperature coefficient of resistance according to claim 1 x A method for preparing a MXene / graphite composite conductive ink, characterized in that In step 32, the stirring speed is controlled to be 300-2000 r / min, and the stirring time is 0.5-12 h.

9. The Ti3C2T3O4 composite material having a low temperature coefficient of resistance according to claim 1 x A method for preparing a MXene / graphite composite conductive ink, characterized in that In the step 33, the stirring speed is controlled to be 300 to 2000 r / min, and the stirring time is 0.5 to 12 h.

10. The Ti3C2T3O4 composite material having a low temperature coefficient of resistance according to claim 1 x A method for preparing a MXene / graphite composite conductive ink, characterized in that In the steps three and four, the stirring speed is controlled to be 300 to 2000 r / min, and the stirring time is 0.5 to 12 h.